Structural basis for 16S ribosomal RNA cleavage by the cytotoxic domain of colicin E3. - Ng, C; Lang, K; Meenan, N; Sharma, A; Kelley, A; Kleanthous, K; Ramakrishnan, V (2010)
The toxin colicin E3 targets the 30S subunit of bacterial ribosomes and cleaves a phosphodiester bond in the decoding center. We present the crystal structure of the 70S ribosome in complex with the cytotoxic domain of colicin E3 (E3-rRNase). The structure reveals how the rRNase domain of colicin binds to the A site of the decoding center in the 70S ribosome and cleaves the 16S ribosomal RNA (rRNA) between A1493 and G1494. The cleavage mechanism involves the concerted action of conserved residues Glu62 and His58 of the cytotoxic domain of colicin E3. These residues activate the 16S rRNA for 2' OH-induced hydrolysis. Conformational changes observed for E3-rRNase, 16S rRNA and helix 69 of 23S rRNA suggest that a dynamic binding platform is required for colicin E3 binding and function.